"A room of one's own(?)" in battlespace – women soldiers in war rooms. Issue 1 (2nd January 2021) - Harel-Shalev, Ayelet
ABSTRACT: At present, women serve in a variety of combat roles and combat support positions in various militaries around the globe. In parallel, new technologies of warfare are transferring more and more soldiers, including women, from the sidelines into the heart of the battlespace. More women soldiers are thus becoming significant participants in war by virtue of their assignment to strategic war rooms. As one of the women soldiers interviewed in this study explained: 'In the war-room, you see everything. You see more than the soldiers in the field see; you see the whole picture'. Even though such women soldiers are not located physically in the battlefield, they do indeed participate in warfare by promoting 'security' for their countries and for their comrades in arms and by being responsible for injuring the 'other'. The stationing of women in war rooms located on the borders of conflict zones, which are equipped with the latest technologies that bring the reality of the warzone into the war room, may challenge traditional concepts of security, war, and gender roles. The narratives of women soldiers serving in such war rooms can thus provide critical insights into 'experiencing war' and 'making war' in battlespace. Personal interviews with 30 Israeli women whose mandatory military service was spent in war rooms revealed multiple narratives of war, including the intertwining of protection, security, and insecurity. The paper thus sheds new light on the role of women in the military by exploring women 'in a room of their own' in battlespace.